MANAJEMEN PENGELOLAAN HARTA KEKAYAAN PADA PENGUSAHA MUSLIM DI MARTAPURA PERSPEKTIF EKONOMI SYARIAH - Akhmad Hulaify; Syahrani Syahrani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Wealth management in moslem’s enterprenuer at Martapura is an orientation of this research. Besed on wealth management concept, the researcher try to explore how is their the wealth management concept so that their wealth bring blessings. The aim of this research to gire more explanation related on wealth management concept that done by moslem’s enterprenuer at Martapura. This research is a field research. Because of this research choices Martapura Kabupaten Banjar, so for reveling the problem, research apply sosiologic normative approach. in revaling and analyze the problem, research apply qualitative description opproach. So will found the answer from real condition that happened in the field. A series of those process make a description that thereaded (concatenated description) so easy to understand. The cunclosion of this research is moslem’s enterprenuer at Martapura have wealth management concept the oriented to Allah SWT’s blessings. So the steep and management schemesthat they did in eccordance with syari’s laws. But in orther side, there are several things that need to be anhanched aspecially, related to the management of incoe rest. They have preference in using to distribute directty better to allocated their fund in long term investment. So concept “Falah” in syariah economic understanding can be reached.Keywords : Management, Wealth, Moslem’s, Enterprenuers.